Serological survey on the prevalence of chicken infectious anemia virus in broiler breeder and layer farms in some selected areas of Bangladesh - Kabir, Md Al Arif; Saha, Sukumar; Hossain, Md Golzar; Khan, Kamrul Ahmed; Islam, Md Alimul; Rahman, Lutfor (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: Chicken infectious anemia virus (CIAV) is an economically important emerging infection of poultry as it causes immunosuppression and reduces egg production. Although it is worldwide distributed and first reported (single case) in Bangladesh in 2002, no epidemiological and serological investigations have been conducted. The current study aimed to conduct a serological investigation on the prevalence of CIAV infection in broiler breeder and layer farms in some selected areas of Bangladesh. Materials and Methods: A total number of 460 sera samples were randomly collected from unvaccinated broiler breeder and layer flocks, of which 276 were from 11 broiler breeder farms and 184 from 12 layer farms. The sera samples were subjected to a commercially available enzyme-linked immunosorbent assay kit to observe antibodies induced by CIAV. Results: Results demonstrated that the overall prevalence of CIAV was 83.6% among a total of 460 samples. In broiler breeder birds, the prevalence was 89.9%, whereas it was 78.3% in layer birds. A higher number of female birds was found to be seropositive than male birds. However, chickens of all age groups were found to be susceptible to the virus. Conclusions: These results indicate the presence of CIAV in Bangladesh, which may be the sequel of naturally occurring either vertical or horizontal infection in all bird flocks tested without clinical symptoms of the disease. A further epidemiological investigation will be required, followed by molecular isolation and characterization of the virus for suitable vaccine candidate selection and/ or preparation. J. Adv. Vet. Anim. Res., 8(2): 323-329, June 2021